CWA CH 0R FINAL_97_09 - Chapter R ALGEBRA REFERENCE 9(3t...

Info icon This preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
Chapter R ALGEBRA REFERENCE R.1 Polynomials 1. (2 x 2 ¡ 6 x + 11) + ( ¡ 3 x 2 + 7 x ¡ 2) = 2 x 2 ¡ 6 x + 11 ¡ 3 x 2 + 7 x ¡ 2 = (2 ¡ 3) x 2 + (7 ¡ 6) x + (11 ¡ 2) = ¡ x 2 + x + 9 2. ( ¡ 4 y 2 ¡ 3 y + 8) ¡ (2 y 2 ¡ 6 y ¡ 2) = ( ¡ 4 y 2 ¡ 3 y + 8) + ( ¡ 2 y 2 + 6 y + 2) = ¡ 4 y 2 ¡ 3 y + 8 ¡ 2 y 2 + 6 y + 2 = ( ¡ 4 y 2 ¡ 2 y 2 ) + ( ¡ 3 y + 6 y ) + (8 + 2) = ¡ 6 y 2 + 3 y + 10 3. ¡ 6(2 q 2 + 4 q ¡ 3) + 4( ¡ q 2 + 7 q ¡ 3) = ( ¡ 12 q 2 ¡ 24 q + 18) + ( ¡ 4 q 2 + 28 q ¡ 12) = ( ¡ 12 q 2 ¡ 4 q 2 ) + ( ¡ 24 q + 28 q ) + (18 ¡ 12) = ¡ 16 q 2 + 4 q + 6 4. 2(3 r 2 + 4 r + 2) ¡ 3( ¡ r 2 + 4 r ¡ 5) = (6 r 2 + 8 r + 4) + (3 r 2 ¡ 12 r + 15) = (6 r 2 + 3 r 2 ) + (8 r ¡ 12 r ) + (4 + 15) = 9 r 2 ¡ 4 r + 19 5. (0 : 613 x 2 ¡ 4 : 215 x + 0 : 892) ¡ 0 : 47(2 x 2 ¡ 3 x + 5) = 0 : 613 x 2 ¡ 4 : 215 x + 0 : 892 ¡ 0 : 94 x 2 + 1 : 41 x ¡ 2 : 35 = ¡ 0 : 327 x 2 ¡ 2 : 805 x ¡ 1 : 458 6. 0 : 5(5 r 2 + 3 : 2 r ¡ 6) ¡ (1 : 7 r 2 ¡ 2 r ¡ 1 : 5) = (2 : 5 r 2 + 1 : 6 r ¡ 3) + ( ¡ 1 : 7 r 2 + 2 r + 1 : 5) = (2 : 5 r 2 ¡ 1 : 7 r 2 ) + (1 : 6 r + 2 r ) + ( ¡ 3 + 1 : 5) = 0 : 8 r 2 + 3 : 6 r ¡ 1 : 5 7. ¡ 9 m (2 m 2 + 3 m ¡ 1) = ¡ 9 m (2 m 2 ) ¡ 9 m (3 m ) ¡ 9 m ( ¡ 1) = ¡ 18 m 3 ¡ 27 m 2 + 9 m 8. (6 k ¡ 1)(2 k ¡ 3) = (6 k )(2 k ) + (6 k )( ¡ 3) + ( ¡ 1)(2 k ) + ( ¡ 1)( ¡ 3) = 12 k 2 ¡ 18 k ¡ 2 k + 3 = 12 k 2 ¡ 20 k + 3 9. (3 t ¡ 2 y )(3 t + 5 y ) = (3 t )(3 t ) + (3 t )(5 y ) + ( ¡ 2 y )(3 t ) + ( ¡ 2 y )(5 y ) = 9 t 2 + 15 ty ¡ 6 ty ¡ 10 y 2 = 9 t 2 + 9 ty ¡ 10 y 2 10. (9 k + q )(2 k ¡ q ) = (9 k )(2 k ) + (9 k )( ¡ q ) + ( q )(2 k ) + ( q )( ¡ q ) = 18 k 2 ¡ 9 kq + 2 kq ¡ q 2 = 18 k 2 ¡ 7 kq ¡ q 2 11. μ 2 5 y + 1 8 z ¶ μ 3 5 y + 1 2 z = μ 2 5 y ¶ μ 3 5 y + μ 2 5 y ¶ μ 1 2 z + μ 1 8 z ¶ μ 3 5 y + μ 1 8 z ¶ μ 1 2 z = 6 25 y 2 + 1 5 yz + 3 40 yz + 1 16 z 2 = 6 25 y 2 + μ 8 40 + 3 40 yz + 1 16 z 2 = 6 25 y 2 + 11 40 yz + 1 16 z 2 12. μ 3 4 r ¡ 2 3 s ¶ μ 5 4 r + 1 3 s = μ 3 4 r ¶ μ 5 4 r + μ 3 4 r ¶ μ 1 3 s + μ ¡ 2 3 s ¶ μ 5 4 r + μ ¡ 2 3 s ¶ μ 1 3 s = 15 16 r 2 + 1 4 rs ¡ 5 6 rs ¡ 2 9 s 2 = 15 16 r 2 ¡ 7 12 rs ¡ 2 9 s 2 13. (2 ¡ 3 x )(2 + 3 x ) = (2)(2) + (2)(3 x ) + ( ¡ 3 x )(2) + ( ¡ 3 x )(3 x ) = 4 + 6 x ¡ 6 x ¡ 9 x 2 = 4 ¡ 9 x 2 14. (6 m + 5)(6 m ¡ 5) = (6 m )(6 m ) + (6 m )( ¡ 5) + (5)(6 m ) + (5)( ¡ 5) = 36 m 2 ¡ 30 m + 30 m ¡ 25 = 36 m 2 ¡ 25 29
Image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
30 Chapter R ALGEBRA REFERENCE 15. (3 p ¡ 1)(9 p 2 + 3 p + 1) = (3 p ¡ 1)(9 p 2 ) + (3 p ¡ 1)(3 p ) + (3 p ¡ 1)(1) = 3 p (9 p 2 ) ¡ 1(9 p 2 ) + 3 p (3 p ) ¡ 1(3 p ) + 3 p (1) ¡ 1(1) = 27 p 3 ¡ 9 p 2 + 9 p 2 ¡ 3 p + 3 p ¡ 1 = 27 p 3 ¡ 1 16. (3 p + 2)(5 p 2 + p ¡ 4) = (3 p )(5 p 2 ) + (3 p )( p ) + (3 p )( ¡ 4) + (2)(5 p 2 ) + (2)( p ) + (2)( ¡ 4) = 15 p 3 + 3 p 2 ¡ 12 p + 10 p 2 + 2 p ¡ 8 = 15 p 3 + 13 p 2 ¡ 10 p ¡ 8 17. (2 m + 1)(4 m 2 ¡ 2 m + 1) = 2 m (4 m 2 ¡ 2 m + 1) + 1(4 m 2 ¡ 2 m + 1) = 8 m 3 ¡ 4 m 2 + 2 m + 4 m 2 ¡ 2 m + 1 = 8 m 3 + 1 18. ( k + 2)(12 k 3 ¡ 3 k 2 + k + 1) = k (12 k 3 ) + k ( ¡ 3 k 2 ) + k ( k ) + k (1) + 2(12 k 3 ) + 2( ¡ 3 k 2 ) + 2( k ) + 2(1) = 12 k 4 ¡ 3 k 3 + k 2 + k + 24 k 3 ¡ 6 k 2 + 2 k + 2 = 12 k 4 + 21 k 3 ¡ 5 k 2 + 3 k + 2 19. ( x + y + z )(3 x ¡ 2 y ¡ z ) = x (3 x ) + x ( ¡ 2 y ) + x ( ¡ z ) + y (3 x ) + y ( ¡ 2 y ) + y ( ¡ z ) + z (3 x ) + z ( ¡ 2 y ) + z ( ¡ z ) = 3 x 2 ¡ 2 xy ¡ xz +3 xy ¡ 2 y 2 ¡ yz +3 xz ¡ 2 yz ¡ z 2 = 3 x 2 + xy + 2 xz ¡ 2 y 2 ¡ 3 yz ¡ z 2 20. ( r + 2 s ¡ 3 t )(2 r ¡ 2 s + t ) = r (2 r ) + r ( ¡ 2 s ) + r ( t ) + 2 s (2 r ) + 2 s ( ¡ 2 s ) + 2 s ( t ) ¡ 3 t (2 r ) ¡ 3 t ( ¡ 2 s ) ¡ 3 t ( t ) = 2 r 2 ¡ 2 rs + rt + 4 rs + 2 st ¡ 6 rt + 6 st ¡ 3 t 2 + 2 rt ¡ st + t 2 = 2 r 2 + 2 rs ¡ 5 rt ¡ 4 s 2 + 8 st ¡ 3 t 2 21. ( x + 1)( x + 2)( x + 3) = [ x ( x + 2) + 1( x + 2)]( x + 3) = £ x 2 + 2 x + x + 2 ¤ ( x + 3) = £ x 2 + 3 x + 2 ¤ ( x + 3) = x 2 ( x + 3) + 3 x ( x + 3) + 2( x + 3) = x 3 + 3 x 2 + 3 x 2 + 9 x + 2 x + 6 = x 3 + 6 x 2 + 11 x + 6 22. ( x ¡ 1)( x + 2)( x ¡ 3) = [ x ( x + 2) + ( ¡ 1)( x + 2)]( x ¡ 3) = ( x 2 + 2 x ¡ x ¡ 2)( x ¡ 3) = ( x 2 + x ¡ 2)( x ¡ 3) = x 2 ( x ¡ 3) + x ( x ¡ 3) + ( ¡ 2)( x ¡ 3) = x 3 ¡ 3 x 2 + x 2 ¡ 3 x
Image of page 2
Image of page 3
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

What students are saying

  • Left Quote Icon

    As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

    Student Picture

    Kiran Temple University Fox School of Business ‘17, Course Hero Intern

  • Left Quote Icon

    I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

    Student Picture

    Dana University of Pennsylvania ‘17, Course Hero Intern

  • Left Quote Icon

    The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

    Student Picture

    Jill Tulane University ‘16, Course Hero Intern